Опыт использования электронных сетевых учебно-методических комплексов дисциплин для студентов геологических и нефтяных специальностей вузов - Михеева, Е. В.; Пикула, Н. П. (My University, 2014)
Разработаны и реализуются модульно-дистанционные электронные сетевые учебно-методические комплексы дисциплин «Физическая и коллоидная химия» и «Метрология, стандартизация и сертификация» для обучения студентов геологических, нефтяных и химических направлений с использованием через Интернет систем управления обучением (LMS – Learning Management System).

Modular and remote electronic network educational and methodical complexes of disciplines "Physical and colloidal chemistry" and "Metrology, standardization and certification" for training of students of the geological, oil and chemical directions with use on the Internet of learning management systems (LMS – Learning Management System) are developed and are realized.
Experience of use of electronic network education and methodical complexes of disciplines for students of geological and oil specialties of higher education institutions
Keywords: дистанционное обучение; distance learning; физическая химия; physical chemistry; коллоидная химия; colloidal chemistry; метрология; metrology; стандартизация; standardization; сертификация; certification; модульная объектно-ориентированная динамическая обучающая среда; the modular object-oriented dynamic learning environment